Engineering of Two-dimensional Cobalt-Glycine Complex Thin Sheets of Vertically Aligned Nanosheet Basic Building Blocks for High Performance Supercapacitor Electrode Materials. (20th August 2016) - Hou, Xiaohuan; Chen, Lingyun; Xu, Han; Zhang, Qing; Zhao, Chenglan; Xuan, Liying; Jiang, Yuqian; Yuan, Yuan
Graphical abstract: Highlights: Simple and effective approach of direct hydrothermal decomposition. Novel structures of transparent pink 2D thin sheets. High specific capacity of 879.1 C g −1 at 1 A g −1 and even 547.7 C g −1 at a high rate of 20 A g −1 . Excellent cycling stability of 99.5% capacitance retention after 2000 cycles. Abstract: Novel pink two-dimensional (2D) cobalt-glycine complex thin sheets (CQU-Chen-Gly-Co-3-1) of vertically aligned nanosheet basic building blocks have been successfully synthesized by direct hydrothermal decomposition of the mixed aqueous solution of glycine (Gly) and cobalt (II) nitrate hexahydrate (Co(NO3 )2 6H2 O). Due to their amorphous structure, hierarchical architecture and interconnected porosity, as well as the synergistic effect between their compositions, the as-prepared CQU-Chen-Co-Gly-3-1 thin sheets exhibit excellent pseudocapacitive performance and remarkable cycling stability in an alkaline medium, holding great promise in supercapacitors (SCs). The electrochemical properties were evaluated by cyclic voltammetry (CV), galvanostatic charge–discharge measurement (CP) and electrochemical impedance spectroscopy (EIS) in 6.0 M KOH solution. The CQU-Chen-Gly-Co-3-1-based electrode exhibited a specific discharge capacity as high as 879.1 C g −1 at 1 A g −1 and even 547.7 C g −1 at a high rate of 20 A g −1 through a voltage range of 0.35 V, and average discharge capacitance of 2511.6 and 1564.8 F g −1 at 1 and 20 A g −1, respectively. The materials also exhibited superior charge–discharge stability and maintained 99.5% of its initial capacitance after 2000 continuous charge–discharge cycles at a current density of 10 A g −1 . This simple design and facile synthesis provides an effective strategy to construct SCs electrode materials with enhanced battery-type of capacitive performance and shows promising potential for a wide range of applications in energy storage.